Functional analysis of the SAP30 gene and its relation to muscle development - Petry, Bruna (2021)
Understanding the molecular machinery involved in certain traits of economic interest is important because the genetic information can be applied to animal breeding programs, defining greater accuracy in genomic selection. GWAS studies have identified general QTL and CNV regions on chromosome 4 in Gallus gallus species, in a Brazilian broiler population, associated with muscle development traits such as weight and percentage of breast. Searches for candidate genes present in these regions and that could be participating in muscle development were performed. The SAP30 gene was identified as a possible candidate for muscle development. Therefore, and to validate its function, SAP30 was edited using CRISPR/Cas9 and had its expression reduced by means of siRNA, in myoblast culture in vitro. After these analyses, morphometric analyzes were performed in cell culture to evaluate changes in the area size of these cells. Subsequently, RNA sequencing, differentially expressed genes and functional enrichment analyzes were performed to investigate gene networks and biological processes that mutations and/or reduced expression of SAP30 would be causing. The results for both papers presented the involvement of SAP30 in muscle cell hypertrophy. Both the reduction in gene expression and the induction of mutations in its sequence made the myotubes have a larger area in the treated groups when compared to controls. RNA sequencing analyzes revealed, for both, an important difference in the expression of genes related to muscle development, as well as genes that act in muscle formation and regeneration pathways. So, for the first time, we present the SAP30 gene as a possible regulator of muscle hypertrophy.